2013
DOI: 10.1016/j.crohns.2012.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab trough levels may predict sustained response to infliximab in patients with Crohn's disease

Abstract: During a median follow up of 2 years sustained response to infliximab was observed in slightly more than half of CD patients. Infliximab TL>3μg/ml at the start of maintenance regime were predicative of sustained response to infliximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(159 citation statements)
references
References 22 publications
8
144
1
6
Order By: Relevance
“…) and also higher than those reported in other immune-mediated inflammatory diseases [35][36][37]. Consequently, it will be of interest to study whether a lower dose would achieve the same results in patients with active disease.…”
Section: Discussionmentioning
confidence: 87%
“…) and also higher than those reported in other immune-mediated inflammatory diseases [35][36][37]. Consequently, it will be of interest to study whether a lower dose would achieve the same results in patients with active disease.…”
Section: Discussionmentioning
confidence: 87%
“…Trough levels of infliximab and antibodies to infliximab are increasingly used to monitor treatment and prevent loss of response. 22 However, this data was not available in this retrospective study. On the other hand, 1-year response taking into account the patients that had a recaptured response during the year was not associated with duration of CD.…”
Section: Discussionmentioning
confidence: 87%
“…Timing of removal of seton is not consensual. 31,32 Potential limitations of the study were the number of study centres (22), a long study period with a change of prescription trends and retrospective acquisition of data. In order to limit biases, we took into account the centre effect by using a clustered analysis in the Cox model, and verified that the calendar year of IFX initiation was not associated with outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A Czech study has shown that an infliximab (IFX) trough level of >3 μg/mL at the start of maintenance therapy was associated with sustained clinical response over a 2‐year follow‐up period 11. Similarly for adalimumab (ADL), Karmiris et al .…”
Section: Introductionmentioning
confidence: 99%